Improving the Professional Competence of Arabic Language Teachers through Independent Curriculum Training - Siti Shalihah; Ahmad Faroji; Nuroh Nuroh; Badr Nasser Aljabr (Jurnal Al Bayan: Jurnal Jurusan Pendidikan Bahasa Arab)
Arabic teachers at MTs and MA Al-Muchlisin face challenges in applying the independent curriculum, which focuses on differentiated, project-based, and competency-based learning. A qualitative case study approach was used in this research. The research methodology utilized in this study was Action Research in the form of School Action Research approach using the Kemmis and McTaggart cycle model, which has planning, action, observation, and reflection stages. The subject of the study was Arabic language teachers at MTs and MA Al-Muchlisin who have at least three years of teaching experience but have not yet explored the implementation of the independent curriculum. The independent curriculum training has been effective in enhancing teachers' understanding and skills. Teachers are now able to create teaching modules, design project-based learning, and use differentiated approaches based on students' learning styles (visual, auditory, kinesthetic). They have also improved classroom management, created a more enjoyable learning environment, and focused on evaluating students' competency achievement. The result showed that teacher competence has positively impacted the quality of Arabic language learning which also increased the students’ engagement and motivation. The challenges and obstacles such as varied student abilities and time limitations can be addressed through remedial learning and mentoring. This article recommends the continuous training to ensure the sustainability of the implementation of the independent curriculum and the optimization of learning quality.